High-intensity Interval Training Frequency: Cardiometabolic Effects and Quality of Life. - Stavrinou, Pinelopi S; Bogdanis, Gregory C; Giannaki, Christoforos D; Terzis, Gerasimos; Hadjicharalambous, Marios (Int J Sports Med, 2018)
The effects of high intensity interval training (HIIT) frequency on cardiometabolic health and quality of life were examined in 35 healthy inactive adults (age: 31.7±2.6 yrs, VOpeak: 32.7±7.4 ml·: kg ·: min). Participants were randomly assigned to a control (CON) and two training groups, which performed 10×60-s cycling at ~83% of peak power, two (HIIT-2) or three times per week (HIIT-3) for eight weeks. Compared with CON, both training regimes resulted in similar improvements in VOpeak (HIIT-2: 10.8%, p=0.048, HIIT-3: 13.6%, p=0.017), waist circumference (HIIT-2: -1.4 cm, p=0.048, HIIT-3: -2.4 cm, p=0.028), thigh cross-sectional area (HIIT-2: 11.4 cm, p=0.001, HIIT-3: 9.3 cm, p=0.001) and the physical health component of quality of life (HIIT-2: 8.4, p=0.001, HIIT-3: 12.2, p=0.001). However, HIIT-3 conferred additional health-related benefits by reducing total body and trunk fat percentage (p<0.05, compared with CON), total cholesterol and low-density lipoprotein-cholesterol (p<0.02, compared with CON) and by improving the mental component of quality of life (p=0.045, compared with CON). In conclusion, performing HIIT only twice per week is effective in promoting cardiometabolic health-related adaptations and quality of life in inactive adults. However, higher HIIT frequency is required for an effect on fat deposits, cholesterol and mental component of well-being.
Keywords: Adult; Blood Glucose; Body Fat Distribution; Body Mass Index; Body Weight; Cardiorespiratory Fitness; Cholesterol; Cholesterol, LDL; Female; High-Intensity Interval Training; Humans; Insulin; Male; Oxygen consumption; Quality of Life; Time Factors; Waist Circumference